the The Role of Ultrasound in the Diagnosis of Malignant Thyroid Nodules - Sulaiman, Tharwat I; Sarsam, Maan K.; muhammed, ammar noori (Journal of the Faculty of Medicine Baghdad, 2020)
Background: Thyroid nodules are very common in clinical practice. Although most of thyroid nodules are benign, it is crucial to checkout which nodules are more likely to be malignant. Ultrasound is a major diagnostic tool for screening and evaluating thyroid diseases because it is safe, non-invasive, non-radioactive and effective.Objective: The aim is to identify the role of ultrasound in assessing thyroid nodules and to review various ultrasound criteria predicting malignancy.Patients and methods: A case series study conducted during the period from January 2015 to February 2016 at the First Surgical Unit, Department of Surgery, Baghdad Teaching Hospital by a team of surgeons. One hundred eighty Patients who underwent surgical intervention for nodular thyroid disease were included in the study. The ultrasound features of these patients were analyzed with respect to the number of nodules (solitary or multiple), size, echogenicity, consistency, the presence of calcification, border definition, vascular pattern and whether there was lymphadenopathy and / or local invasion to adjacent structures. The final diagnosis was confirmed by histopathological examination after surgery. The ultrasound features of thyroid nodules were studied for their correlation with benign and malignant lesions.Results: Among 180 patients with nodular thyroid disease, thyroid malignancy was found in 22 (12.2%) patients. Ultrasound features of thyroid nodules included significant echogenicity, consistency, calcification, border definition, vascular pattern and the presence of local invasion. Ultrasound features suggesting malignant nodules are solid and hypoechoic nodules, ill-defined borders, nodules with local invasion to adjacent structures, the presence of microcalcification and nodules that show increased vascularity on doppler study.Conclusion: Ultrasound is useful in evaluating nodular thyroid disease and is valuable for identifying many malignant and potentially malignant nodules. Despite that, no single ultrasound feature is reliable in making the diagnosis of thyroid malignancy, combining ultrasound suggestive criteria could aid in predicting malignant nature of a given nodule.